Orientasi Pemasaran Hijau dan Kemasan Ramah Lingkungan Menuju Tujuan Pembangunan Berkelanjutan: Studi Empiris Konsumen Makanan Organik di Kota Bandung - Triana Ananda Rustam; Ananda Mellyssa Quratul Ain; Debby Kania Bustami (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2025)
This study examines the impact of green marketing orientation and eco-packaging on sustainable consumption behavior among organic food consumers in Bandung. The research investigates six dimensions of green marketing orientation (green product orientation, green promotion orientation, and green ethical commitment) and three dimensions of eco-packaging (material sustainability, packaging functionality, and environmental information on packaging). Data were collected from 120 respondents who had purchased organic food products using a structured questionnaire. Multiple linear regression analysis was conducted to test the proposed hypotheses. The results reveal that green product orientation, green promotion orientation, green ethical commitment, material sustainability, and environmental information on packaging significantly influence sustainable consumption behavior. However, packaging functionality did not show a significant effect. These findings highlight the importance of product-related sustainability attributes, ethical communication, and eco-friendly packaging in influencing consumer behavior. The study contributes to the literature by providing empirical evidence from an Indonesian urban context and offers insights for businesses to enhance their sustainability strategies.